A Case study on the role of interior design in Muslim worship in the home Erielle B. Ekong ; Johanna Victoria A. Faustino, adviser. - Ekong, Erielle B. (College of Home Economics, University of the Philippines Diliman, 2020)
This case study attempts to describe the role of interior design in the experience of Muslim worship since there are no direct guidelines specified by Islam in designing worship spaces in residential homes. A qualitative research design was used and the sampling method for the study is purposive wherein the sample were five practicing and religious Muslims living in Metro Manila. The data gathered from the survey questionnaire were analyzed using secondary sources of information. The study revealed that the Five Pillars of Islam are the fundamental principles practiced by the respondents. Among all the pillars, the performance of the compulsory five times daily prayer is the only practice that is translated in the respondents' prayer areas at home. The respondents can pray in any clean and quiet place for as long as they are able to perform the ritual ablution, face the direction of the Ka'bah and be fully concentrated, such as in the bedroom and living room. The findings also revealed that interior design plays experiential and functional roles in Muslim worship, wherein sound quality, color, direction in prayer, thermal comfort, and privacy improve respondents' comfort and focus during prayer and other religious practices, while light, Islamic ornamentation, size of area, and flexibility of space provide support during the respondents' observance of religious obligations and attain the concentration needed in Muslim worship. Muslims pray at five different times of the day, therefore the changes in time regarding the physical environment and the experience of the respondent were included in the study. The Filipino culture of shared spaces is also a factor in the respondents' worship at home. The findings also revealed that the most important factor in designing a home that is centered on Muslim worship is to identify the best area where prayers and other religious practices will be performed.